Gaze aversion in conversational settings: An investigation based on mock job interview - Cengiz Acarturk; Bipin Indurkya; Piotr Nawrocki; Bartlomiej Sniezynski; Mateusz Jarosz; Kerem Alp Usal (Bern Open Publishing, 2021)
We report the results of an empirical study on gaze aversion during dyadic human-to-human conversation in an interview setting. To address various methodological challenges in as- sessing gaze-to-face contact, we followed an approach where the experiment was conducted twice, each time with a different set of interviewees. In one of them the interviewer's gaze was tracked with an eye tracker, and in the other the interviewee's gaze was tracked. The gaze sequences obtained in both experiments were analyzed and modeled as Discrete-Time Markov Chains. The results show that the interviewer made more frequent and longer gaze contacts compared to the interviewee. Also, the interviewer made mostly diagonal gaze aversions, whereas the interviewee made sideways aversions (left or right). We discuss the relevance of this research for Human-Robot Interaction, and discuss some future research problems.